2020
DOI: 10.1128/mbio.03185-20
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant ACE2 Expression Is Required for SARS-CoV-2 To Infect Primary Human Endothelial Cells and Induce Inflammatory and Procoagulative Responses

Abstract: SARS-CoV-2 causes COVID-19, an acute respiratory distress syndrome (ARDS) characterized by pulmonary edema, viral pneumonia, multiorgan dysfunction, coagulopathy, and inflammation. SARS-CoV-2 uses angiotensin-converting enzyme 2 (ACE2) receptors to infect and damage ciliated epithelial cells in the upper respiratory tract. In alveoli, gas exchange occurs across an epithelial-endothelial barrier that ties respiration to endothelial cell (EC) regulation of edema, coagulation, and inflammation. How SARS-CoV-2 dys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 30 publications
7
60
0
Order By: Relevance
“…HCMVEC, HLMVEC, HUVEC and HPAEC did not express ACE2 and were not permissive for SARS-CoV-2. However, transducing endothelial cells with recombinant ACE2 may enable SARS-CoV-2 infection as shown recently [ 20 ], suggesting that the lack of sufficient ACE2 expression might be a limiting factor. Subsequent steps in the viral life cycle appear to be blocked in HCAECs.…”
Section: Discussionmentioning
confidence: 99%
“…HCMVEC, HLMVEC, HUVEC and HPAEC did not express ACE2 and were not permissive for SARS-CoV-2. However, transducing endothelial cells with recombinant ACE2 may enable SARS-CoV-2 infection as shown recently [ 20 ], suggesting that the lack of sufficient ACE2 expression might be a limiting factor. Subsequent steps in the viral life cycle appear to be blocked in HCAECs.…”
Section: Discussionmentioning
confidence: 99%
“…This gap has now been filled by recently published work by different groups in which isolated human endothelial cells were cultured in the presence of the SARS-CoV-2 virus. Using immunohistochemistry for the N or S protein and a viral progeny detection assay, Nascimento Conde et al showed that SARS-CoV-2 is incapable of infecting primary human endothelial cells from lung, brain, and renal glomeruli as well as HUVEC 50 . Ajmetaj-Shala and coworkers demonstrated that blood outgrowth, lung and aortic primary human endothelial cells were not susceptible to infection by SARS-CoV-2 or SARS-CoV-2 pseudovirus but could be infected with Ebola and Vesicular Stomatitis Virus 49 .…”
Section: Cultured Endothelial Cells Are Resistant To Sars-cov-2 Infectionmentioning
confidence: 99%
“…These abortive infections obtained with high SARS-CoV-2 titers in endothelial cells that do not express the ACE2 receptor or express it weakly have been attributed to engagement by the virus of noncanonical receptors and lack of surface enzymes needed to cleave the S protein and mediate effective viral-host cell membrane fusion 43 , 45 , 47 . Notably, endothelial cells became permissive to SARS-CoV-2 only following transduction with recombinant ACE2 receptor 50 . Thus, in vitro studies with human endothelial cells isolated from different organs have consistently shown that the vascular endothelium is resistant to SARS-CoV-2 infection.…”
Section: Cultured Endothelial Cells Are Resistant To Sars-cov-2 Infectionmentioning
confidence: 99%
“…Even in the presence of inflammation, where an endothelial cell was pretreated with IL-1, the cells remained refractory to SARS-CoV-2 infection. A separate study demonstrated that primary human endothelial cells lack ACE2 receptors at the RNA and protein levels, and that SARS-CoV-2 is incapable of directly infecting endothelial cells from pulmonary, cardiac, kidney, or brain tissues, even after stimulation with a variety of factors (e.g., IL-1β, TNF-α, IL-6) 41 . In contrast, pulmonary endothelial cells transfected with ACE2 receptors can be infected, indicating that endothelial cells are permissive for SARS-CoV-2 replication 41 .…”
Section: Evidence That Covid-19-induced Severe Ards Is a Distinct State Of Endotheliitismentioning
confidence: 99%
“… 27 In contrast, pulmonary endothelial cells transfected with ACE2 receptors can be infected, indicating that endothelial cells are permissive for SARS-CoV-2 replication. 27 …”
Section: Evidence That Covid-19-induced Severe Ards Is a Distinct State Of Endotheliitismentioning
confidence: 99%